Integrated reporting : inspiring companies to integrate sustainability into their business strategy and practice? - Goldman, Jonny (Department of Environmental and Geographical Science, 2015)
This research focuses on the potential convergence between the 'form' of corporate sustainability (CS), represented by selected South African companies' integrated reports (IRs), and the underlying 'substance' of CS, being the integration of sustainability into companies' strategy and operations. The research also explores the extent to which organisational culture and management systems underpin and operationalise integrated reporting (IR) and CS. The research is approached from two perspectives: firstly, the research investigates the strategies and implementation of IR and CS independent of one another, and aims to reveal contemporary IR and CS practice and challenges; secondly, the research focuses on the potential relationship between IR and CS by seeking to identify any synergies between the IR and CS, and aims to provide insight into whether IR can further a company's CS ambitions, and if so, how this occurs. The research follows a case study research methodology, which is considered suitable for research into new fields given its predisposition to theory building. The cases were selected from those included in Ernst & Young's Excellence in Integrated Reporting Awards for 2012 (EY 2012 survey), which reviewed and rated the IRs of the top 100 companies on the Johannesburg Stock Exchange (JSE). The sample includes a total of six companies selected from the above-mentioned top 100 companies, being two companies from each of three JSE super-sectors. Of the two companies in each super-sector, one company was recognised by the EY 2012 survey as having produced a superior integrated report and the other company had not achieved such recognition. A detailed review of each company's two most recent IRs and sustainability report was undertaken to inform and facilitate meaningful and insightful interviews with appropriate personnel from various departments within each company, including corporate affairs and communication; environmental; strategy and business development; finance; sustainability; human resources; governance, risk and compliance; and corporate social investment. Primarily open-ended questions were posed to allow for the collection of qualitative, company- specific information on companies' IR and CS strategies and implementation. The broad-based adoption of IR in South Africa, in response to the JSE regulation requiring listed companies to produce an integrated report or explain why they have not, has provided a sound platform for revealing the early stages of IR practice. Although CS is not a new corporate discipline, it remains a somewhat contested corporate practice, evident from the broad spectrum of companies' approaches to CS: these range from a basic compliance standpoint to more holistic synergistic strategies aimed at integrating CS into all parts of the business. Given the differing approaches to, and appetites for, IR and CS amongst the researched companies, the findings identify certain dominant themes of contemporary practice, and reveal opportunities for expanding and improving IR and CS. Indications are that management systems play an important role in the implementation of IR and CS strategies. IR, a relatively stand-alone corporate function, shows limited dependence on organisational culture, which is a key determinant for CS given its extensive reach within companies and reliance on employee buy-in for engaging with CS. The findings also uncover other key insights into the multi-faceted relationships between IR, CS, organisational culture and management systems. Finally, although there are some synergies between IR and CS, these represent a more subtle, constrained IR and CS relationship. To conclude, although the findings recognise that IR can stimulate a focus on CS in companies that have yet to seriously engage with CS, succeeding in IR does not appear for the most part to provide an indication of proficient CS capability, reflecting a decoupling of IR practice and success from that for CS.